1998
DOI: 10.1111/j.1470-6431.1998.tb00718.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of product‐specific variables on consumers' post‐consumption behaviour for apparel products: USA

Abstract: Companies spend valuable resources developing and distributing products to please the consumer; however, products that do not match consumer performance expectations during post‐purchase use often result in consumer dissatisfaction. This situation can lead to redress‐seeking behaviour and negative repurchase behaviour. Understanding factors influencing consumers' post‐purchase behaviour can provide retailers with information to make accurate purchasing decisions and improve interpretation of the post‐return da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…Singh in Halstead and Dröge (1991) indicated that the normative dimension of attitude ("I should complain") positively and significantly influenced consumers' intention to seek redress. Consumers who have a favourable attitude toward complaining will be more likely to seek redress from the retailer (Beardon & Mason in Blodgett & Granbois, 1992; Singh in Kincade et al, 1998). Consumers' attitudes toward business, government, consumer organisations and complaining have been studied in order to predict complaining behaviour, but the results have been mixed (Barnes & Kelloway, 1980;Halstead & Dröge, 1991).…”
Section: Consumer Complaint Behaviourmentioning
confidence: 99%
See 3 more Smart Citations
“…Singh in Halstead and Dröge (1991) indicated that the normative dimension of attitude ("I should complain") positively and significantly influenced consumers' intention to seek redress. Consumers who have a favourable attitude toward complaining will be more likely to seek redress from the retailer (Beardon & Mason in Blodgett & Granbois, 1992; Singh in Kincade et al, 1998). Consumers' attitudes toward business, government, consumer organisations and complaining have been studied in order to predict complaining behaviour, but the results have been mixed (Barnes & Kelloway, 1980;Halstead & Dröge, 1991).…”
Section: Consumer Complaint Behaviourmentioning
confidence: 99%
“…Both retailers and manufacturers in many cases underestimate the detrimental effect of such indirect activities. Whereas many dissatisfied consumers take these hidden actions instead of directly complaining to formal complaint parties, many consumers who do complain formally also engage in hidden actions (Day et al, 1981;Kincade et al, 1998). Moreover, dissatisfied consumers will typically tell eight to ten people about their problem (Plymire, 1991;Sanes, 1993).…”
Section: Consumer Complaint Behaviourmentioning
confidence: 99%
See 2 more Smart Citations
“…Some consumers may both engage in formal and hidden actions together (Kincade, Giddings and Chenyu, 1998).…”
Section: Figure 1: Classification Of Consumer Complaining Behaviormentioning
confidence: 99%